« C’est ça le futur des soirées ? » Les musiques électroniques de danse à l’épreuve du livestream et de la COVID-19 - Frédéric Trottier-Pistien (Communiquer)
Music livestream reached a new step due to lockdown and the cancellation and prohibition of music events worldwide. EDM market grabbed and articulated it to make “their” new place for music. Through the ethnography of a home-alone party, I will describe an online music festival, using interfaces to cross Detroit and reach the world within Twitch. By giving elements about how a music event producer and broadcasting networks work together, I will map music industry layers. Especially, I will question how audience —a talkative chat and silent viewers—and DJ act and build livestream as a music place, and test how musical is human learning about connexion, community sense, (a)knowledgment and relationship in livestream model comparing to rave or club.